27
$\begingroup$

I need to prove that the equation $x^2 + y^2 = z^3$ has infinitely many solutions for positive $x, y$ and $z$. I got to as far as $4^3 = 8^2$ but that seems to be of no help.

Can some one help me with it?

$\endgroup$
  • 2
    $\begingroup$ Hint: $4^3 = 8^2$, and similarly $16^3 = 64^2$, $64^3 = 512^2$, $\ldots$, so if you have one solution, how can you multiply $x$, $y$ and $z$ by something to get new solutions? $\endgroup$ – ferson2020 Mar 19 '13 at 15:43
  • $\begingroup$ nope it is supposed to be z^3 $\endgroup$ – noddy Mar 19 '13 at 15:44
  • $\begingroup$ @ferson2020 thats correct but i would need to prove that 8^2, 64^2 ... can be expressed as a sum of 2 squares, which i think is not possible. Can you help me with that $\endgroup$ – noddy Mar 19 '13 at 15:46
  • $\begingroup$ The OP's result also follows from the Brahmagupta-Fibonacci identity which says that the set of integers expressible as the sum of two squares is closed under multiplication. In particular, it is closed under positive powers. $\endgroup$ – user940 Mar 19 '13 at 16:19
  • 2
    $\begingroup$ @noddy Take a single solution ($2^2 + 2^2 = 2^3$) and multiply $x$ and $y$ by something ($8, 64, 512, \ldots$) and $z$ by something else ($4, 16, 64, \ldots$) to get a new solution. $\endgroup$ – ferson2020 Mar 19 '13 at 17:42
36
$\begingroup$

Take any Pythagorean triplet $(a,b,c)$.

$$\begin{align*} a^2+b^2 &=c^2\\ a^2\cdot c^4+b^2\cdot c^4&=(c^2)^3\\ (ac^2)^2+(bc^2)^2 &=(c^2)^3 \end{align*}$$

Multiplying $c^{6k-2}$, where $k$ is a natural number.

$\endgroup$
36
$\begingroup$

As an alternative, you can take any standard Pythagorean triple, e.g. $3^2+4^2=5^2$, and then multiply through by $5^4$ to get:

$$3^2.5^4 + 4^2.5^4 = 5^6$$

i.e.

$$(3.5^2)^2 + (4.5^2)^2 = (5^2)^3$$

which will give an infinite set of solutions.

$\endgroup$
  • 5
    $\begingroup$ +1. This simple trick is so effective in mixed-exponent Fermat-type equations. It's the reason why the Fermat-Catalan conjecture requires solutions to be coprime integers. $\endgroup$ – Erick Wong Mar 19 '13 at 15:58
33
$\begingroup$

$$(a^2+1)^3=a^2(a^2+1)^2+(a^2+1)^2$$

$\endgroup$
27
$\begingroup$

Set $z=a^2+b^2=(a+bi)(a-bi)$, $(i=\sqrt{-1})$

$x^2+y^2=(x+yi)(x-yi)=z^3=(a+bi)^3(a-bi)^3,$

$(1)\quad x+yi=(a+bi)^3=a^3+3a^2bi-3ab^2-b^3i,$

$x=a^3-3ab^2,y=3a^2b-b^3,z=a^2+b^2.$

$(2)\quad x+yi=(a+bi)^2(a-bi)=(a^2+b^2)(a+bi),$

$x=(a^2+b^2)a,y=(a^2+b^2)b,z=a^2+b^2$

$\endgroup$
  • $\begingroup$ This is the solution I was about to submit. $\endgroup$ – Lubin Mar 19 '13 at 17:25
  • $\begingroup$ Elegant solution, +1. $\endgroup$ – Soham Chowdhury Mar 20 '13 at 12:23
15
$\begingroup$

There are already infinitely many solutions among $2^k$'s: $$2^k+2^k=2^{k+1}$$ So, if $k$ is even and $3\,|\,k+1$ (that is, $k\equiv 2\pmod{6}$), then it's a solution.

$\endgroup$
7
$\begingroup$

More generally, if $m$ and $n$ are coprime, the diophantine equation $x^m+y^m=z^n$ has infinitely many integral solutions. See this question. Your question is the specific case of $m=2$ and $n=3$.

$\endgroup$
6
$\begingroup$

If $a^2+b^2=c^3$ is one solution, then for all integers $t$ we have

$$(at^3)^2+(bt^3)^2=(ct^2)^3$$

$\endgroup$
3
$\begingroup$

the equation:

$X^2+Y^2=Z^3$

Has the solutions:

$X=2k^6+8tk^5+2(7t^2+8qt-9q^2)k^4+16(t^3+2qt^2-tq^2-2q^3)k^3+$

$+2(7t^4+12qt^3+6q^2t^2-28tq^3-9q^4)k^2+8(t^5+2qt^4-2q^3t^2-5tq^4)k+$

$+2(q^6-4tq^5-5q^4t^2-5q^2t^4+4qt^5+t^6)$

.................................................................................................................................................

$Y=2k^6+4(3q+t)k^5+2(9q^2+16qt+t^2)k^4+32qt(2q+t)k^3+$

$+2(-9q^4+20tq^3+30q^2t^2+12qt^3-t^4)k^2+4(-3q^5-tq^4+10q^3t^2+6q^2t^3+5qt^4-t^5)k-$

$-2(q^6+4tq^5-5q^4t^2-5q^2t^4-4qt^5+t^6)$

.................................................................................................................................................

$Z=2k^4+4(q+t)k^3+4(q+t)^2k^2+4(q^3+tq^2+qt^2+t^3)k+2(q^2+t^2)^2$

$q,t,k$ - What are some integers any sign. After substituting the numbers and get a result it will be necessary to divide by the greatest common divisor. This is to obtain the primitive solutions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.